ANEMIA IN PREGNANT ADOLESCENTS AS A RISK FACTOR FOR LOWBIRTH WEIGHT IN NEONATES - Azañedo Casanova, Isabel Milagros (2024)
Introduction. Anemia in pregnant adolescents is a growing public health issue. It has been identified as a potential risk factor for low birth weight, a critical indicator of neonatal health. Objective. To determine if anemia in pregnant adolescents is a significant risk factor for low birth weight in neonates. Methodology. An observational-analytical, retrospective case-control study was conducted at Cayetano Heredia Jose Hospital in Piura, from 2017 to 2022. The population included neonates from adolescent mothers aged 15-19 years. A sample size of 236 neonates (59 cases and 177 controls) was based on the prevalence of low birth weight. Inclusion criteria for cases and controls involved recording hemoglobin levels during pregnancy and at term, excluding preterm infants and mothers with pre-existing conditions. Sampling was systematic with matching based on maternal age, gestation time, and parity. Results. No statistically significant association was found between anemia in pregnant adolescents and low birth weight in the studied neonates. Conclusion. Despite the prevalence of anemia in pregnant adolescents, this study did not confirm it as a risk factor for low birth weight in the context studied.